Bad government as a reason of recent financial crisis in Europe - Galooyek, Maryam Jafary; Mohd Noor, Zaleha; Rajabi, Ehsan (International Strategic Management Association, 2014)
In spite of emphasizing on a market by economic liberalism, most experts believe that market failure caused the deepest global crisis after Great Depression (1929) to happen. Although we cannot ignore the importance to the role of attendance of government to the economy, we believe that sometimes governments are the reason behind the problems in economic situation. Factors like the lack of political integration between European governments and cooperation of national government, the absence of mighty government to make decision and policy and undisciplined financial plans, as well as, loss of proper rules and low, which are occasions of bad government.